Contributions to Predictive Control of Static Converters Associated with a Renewable Energy Production System - Mahideb, Saadia (Universty of Eloued جامعة حمه لخضر الوادي, 2021)
الملخص : في هذه الأطروحة قمنا بالجمع بين مفهوم -αمقبولية مع مفاهيم -θتقلص و تقلص من نوع بيرند ) (Berindeلإدخال نوع جديد من التقلصات للحصول على بعض النتائج المرتبطة بالنقطة الثابتة في فضاءات مترية تامة، نستنتج أيضا وجود نقط ثابتة في فضاءات مترية مرتبة جزئيا و فضاءات مترية تامة مزودة ببيان بإستخدام نتائجنا الرئيسية. في الأخير طبقنا النتائج المحصل عليها لإثبات وجود حلول لمسألة القيمة الحدية لمعادلات تفاضلية كسرية مع شروط حدية تكاملي Abstract : In this thesis, we combine the notion of α-admissible mappings with - contraction and Berinde type contraction concepts to introduce a new type of contractions and related fixed point results in complete metric spaces. We also deduce the existence of fixed points in partially ordered metric spaces and in complete metric spaces endowed with a graph by using our main results. Finally, we provide an example and an application to the existence of the solutions for a boundary value problem of fractional differential equations to illustrate the importance of the obtained results.
أطروحة دكتوراه تخصص رياضيات تطبيقية
Keywords: فضاءات مترية، نظرية النقطة الثابتة، -تقلص ،تقلص من نوع بيرند Berinde ، α-مقبولية، معادلات تفاضلية كسرية.; Metrics spaces, theory of fixed point, -contraction, Berinde type contraction, α-admissible, fractional differential equations.